2020
DOI: 10.1038/s41438-020-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the sex locus in Salix triandra confirms a consistent sex determination mechanism in genus Salix

Abstract: Salix triandra belongs to section Amygdalinae in genus Salix, which is in a different section from the willow species in which sex determination has been well studied. Studying sex determination in distantly related willow species will help to clarify whether the sexes of different willows arise through a common sex determination system. For this purpose, we generated an intraspecific full-sib F 1 population for S. triandra and constructed high-density genetic linkage maps for the crossing parents using restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 66 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Further perspectives for understanding functional traits are available via whole-genome sequencing studies. A couple of studies focused so far on sex determination systems in willows [49,65,74], but genome sequencing data will also help to understand functional traits [67].…”
Section: Discussionmentioning
confidence: 99%
“…Further perspectives for understanding functional traits are available via whole-genome sequencing studies. A couple of studies focused so far on sex determination systems in willows [49,65,74], but genome sequencing data will also help to understand functional traits [67].…”
Section: Discussionmentioning
confidence: 99%
“…In willow ( Salix spp. ), the SDR was identified on chromosome 15 with female heterogamety (ZW) in Salix viminalis ( Pucholt et al, 2015 ), Salix suchowensis ( Hou et al, 2015 ; Chen et al, 2016 ), Salix purpurea ( Zhou et al, 2018 ), and Salix triandra ( Li et al, 2020 ). A recent study revealed large palindromic structures on the W chromosome of S. purpurea and an ortholog of ARR17 ( Salix purpurea RESPONSE REGULATOR 9, SpRR9 ) was suggested as a strong candidate gene for sex determination ( Zhou et al, 2020a ).…”
Section: Genetic Mechanisms Of Sex Determinationmentioning
confidence: 99%
“…SSR markers are present in almost all species, particularly in eukaryotes. These markers have many applications, such as constructing linkage maps, fine mapping of genes, and selective breeding through genomic selection 2 , 23 25 . SSRs have become extremely popular for phylogenetic analysis and have expanded our knowledge related to plant breeding 26 28 .…”
Section: Introductionmentioning
confidence: 99%